“Health in the Mirror”: An Unconventional Approach to Unmet Psychological Needs in Oncology - Di Mattei, Valentina E.; Carnelli, Letizia; Taranto, Paola; Bernardi, Martina; Brombin, Chiara; Cugnata, Federica; Noviello, Angela; Currin, Morag; Mangili, Giorgia; Rabaiotti, Emanuela; Sarno, Lucio; Candiani, Massimo (Frontiers in Psychology, 2017)
Background: The aim of this study is to measure the impact of a psychological support program for female cancer patients called “Health in the Mirror”. This support program is composed of three group sessions that address both aesthetic and psychological aspects that accompany cancer and its treatment. The wider objective is to examine whether there is a basis for combining psychosocial support interventions alongside conventional therapies in hospitals. Methods: Eighty-eight female cancer patients were included in this analysis. Patients were asked to complete a battery of tests in order to measure the impact of the program on certain psychological variables including anxiety, depression, body image, self-esteem, and quality of life. Outcome variables were measured at three different time-points: prior to participation, on the last day of the program, and after a three-month follow-up. Results: Participating in the psychosocial support program “Health in the Mirror” determines an improvement in the psychological variables measured. Results revealed a significant reduction in depressive symptoms, anxiety and body image issues, as well as an improvement in self-esteem levels; this suggests that participating in this program could facilitate better adjustment to disease and treatment. Discussion: This study legitimizes the importance of implementing complementary therapies together with conventional therapies; the therapeutic approach to cancer cannot be restricted solely to medical care, but it must consider the patient as a whole person with needs that are not only physical or medical, but also psychological, social, and existential.